Perceptions and health-seeking practices among an urban population of Tamil Nadu, India- A baseline survey - Geetha Mani; Raja Danasekaran; Kalaivani Annadurai (MRIMS Journal of Health Sciences, 2014)
An increasing urban population in India brings to focus the need to improve health care services to meet the demands. Knowledge on health-seeking practices of the target population would be an essential first step to achieve health care for all. This was a short-term survey conducted between January and March 2012 in an urban area of Tamil Nadu. Majority of the participants (92.5%) were aware of health care facilities at accessible distance. But knowledge regarding curative and immunisation services available in the hospitals was inadequate (61.5% and 88.5% respectively). A positive preference towards public facilities was observed. 86% sought hospitals, 4% Over-the-counter drugs and 6% sought home remedies for common illness. Only 73% of the participants had awareness about health insurance schemes, only 23% of the families were covered by health insurance. The health-seeking practices reflected the inadequate awareness related to health services. These findings stress the need for equipping the population with adequate information regarding the availability of services and motivate appropriate utilization.